“ … When the Body is Well, the Soul is Better”: The Case of the Physician Sebastiano Flaminio and the Body in Counter Reformation Italy - Mariani, Giacomo (Reformation, 2025)
The case of the physician Sebastiano Flaminio, tried by the Inquisition in Imola in 1558, comprises an exceptional case study to investigate the transformation of the religious and social control exercised by the Catholic Chruch on Italian society, through the Inquisition, in the aftermath of the shock provoked by the Reformation. Following an initial phase of the Inquisition – with a restless persecution of the reformed groups in Italy and a political use of the religious court inside the highest spheres of the Catholic Church – the Holy Office turned its attention to “sins” and “crimes” that involved the body. The trial against Sebastiano Flaminio was one of the few that played out on the decision taken by Pope Paul IV in November 1557 to include sodomy among the crimes persecuted by the Holy Office. Besides his sexuality, the information collected by the inquisitors in Imola about Flaminio – he was never questioned, or at least nothing survives of his examinations – offers a more complex picture of a misbeliever and materialist.